PERAN PEMERINTAH DALAM MENGAWASI PEREDARAN OBAT KERAS GOLONGAN G TANPA SURAT IZIN EDAR MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (Studi Kasus: Putusan Nomor 874/Pid.Sus/2018/PN.Sda) - Mia Amelia; Anna Maria Tri Anggraini (Jurnal Hukum Adigama, 2020)
Health is government responsibility for the needs of citizens' rights. One of the most important health elements is medicine. But there are times when drugs can harm the health of the wearer if they don't meet the requirements, and are consumed incorrectly. Many business people deliberately produce drugs without getting permission from BPOM. One example of illegal drugs circulating in Indonesia is the LL Pill, there is a composition of Triheksifenidil HCL is a drug that is included in the drug list letter G, which means dangerous if its use without medical supervision. This attracts the attention because this hard drug has been widely circulating in the community and every year it continues to increase without completion which is feared to damage the nation's generation. Law enforcement is still not effective apart from the circulation of hard drug list G without this marketing authorization, one of which is because the sanctions imposed by law enforcers are still very mild, as a result, it will not cause a deterrent effect for business actors who have violated the provisions of Law Number 8 of 1999 concerning Consumer Protection. Drug monitoring is still weak lately, giving birth to the idea to strengthen the authority of BPOM as a government agency that has authority in drug control and should be carried out more optimally and increase intensity in supervision activities in collaboration with the Indonesian National Police and Health Office to eradicate the distribution of hard drugs which is not licensed.